Analisis Perbandingan Konsep Ganti Rugi dalam Hukum Ekonomi Syariah dan Hukum Perdata Indonesia - Sari, Nopita (JURNAL HUKUM SEHASEN, 2025)
This study aims to analyze the concept of compensation from the perspectives of Islamic economic law and Indonesian civil law. Using a normative and comparative legal approach, it examines the principles of responsibility and justice applied within both legal systems. The findings indicate that Indonesian civil law emphasizes financial compensation for material losses, while Islamic economic law highlights moral values, social balance, and public welfare. In Islamic law, compensation is not limited to monetary payment but may also take other forms that ensure fairness and mutual benefit. Conversely, civil law formally regulates compensation in monetary terms as a result of contractual breaches or unlawful acts. The study suggests that integrating Islamic justice values into Indonesia’s legal framework can create a more balanced and humanistic legal system that harmonizes material and moral aspects of civil responsibility